The Aspect of Liberal Feminism in Moana 2 - Trapsilowati, Hilda Junian; Binawan, Heribertus (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study focuses on the depiction of the character of Moana 2 in the context of liberal feminism, particularly in relation to the issue of women's equality and autonomy in the public sphere. The purpose of this study is to identify the form of representation of liberal feminism shown through Moana's character and actions in the film. This study uses a qualitative approach with thematic analysis method. The research data consists of dialogues, images, words, phrases, and sentences contained in the film, which were collected through documentation techniques and repeated observations. Data analysis was carried out through initial coding stages, grouping themes, and thematic interpretation with reference to the framework of the seven main principles of liberal feminism, and supported by secondary sources in the form of relevant books and scientific articles. The results of the study indicate that of the seven main principles of liberal feminism, six principles are clearly represented in Moana's character and actions. These principles include individual autonomy, freedom of choice, moral and rational equality, participation in the public sphere and citizenship, achievement based on merit, and efforts to reform discriminatory practices. These findings confirm that Moana is depicted as an independent, rational female character with leadership capacity equal to that of men, thus this film represents the values ​​of liberal feminism consistently and meaningfully.